PENERAPAN METODE MENYIMAK MENEBAK DALAM PELAJARAN BAHASA INDONESIA DENGAN MATERI PENGGAMBARAN TOKOH PADA SISWA SMPK BUNGA FATIMA LELA SIKKA NTT - Bhaga, Bertholomeus Jawa; Dua Neang, Elisabeth Henderika (Linguistik : Jurnal Bahasa dan Sastra, 2024)
The aim of this research is to describe the application of the guessing listening method in learning Indonesian on character depiction material. In conventional learning, teachers often use the lecture method in this material. The interactions that are built seem stiff and boring. By offering this guessing listening method, it is hoped that it can raise the enthusiasm for learning at SMPK Bunga Fatima Lela students. This research method is descriptive qualitative. The results obtained show that learning Indonesian using the listening and guessing method in character depiction material is very effective and fun. Thus, it can be a recommendation for Indonesian language teachers in applying this method to other materials and classes.